2020
DOI: 10.3390/catal10030308
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Lipase A—Lipase or Esterase?

Abstract: The question of how to distinguish between lipases and esterases is about as old as the definition of the subclassification is. Many different criteria have been proposed to this end, all indicative but not decisive. Here, the activity of lipases in dry organic solvents as a criterion is probed on a minimal α/β hydrolase fold enzyme, the Bacillus subtilis lipase A (BSLA), and compared to Candida antarctica lipase B (CALB), a proven lipase. Both hydrolases show activity in dry solvents and this proves BSLA to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 69 publications
(136 reference statements)
0
21
0
Order By: Relevance
“…Later, Ali et al [19] suggested classifying carboxylic ester hydrolases differently, dividing them into lipolytic esterases (EC 3.1 L) and non-lipolytic esterases (EC 3.1 NL). More recently still, Bracco et al [20] suggested classifying lipases and esterases based on their ability to act in organic solvents that are immiscible in water (e.g., toluene), with low water activity (a w ). In this review, we use the definition whereby lipases hydrolyze triacylglycerols or acyl esters with acyl chains of 10 carbons or more.…”
Section: Lipases: General Features and Classical Strategy Of Immobilizationmentioning
confidence: 99%
“…Later, Ali et al [19] suggested classifying carboxylic ester hydrolases differently, dividing them into lipolytic esterases (EC 3.1 L) and non-lipolytic esterases (EC 3.1 NL). More recently still, Bracco et al [20] suggested classifying lipases and esterases based on their ability to act in organic solvents that are immiscible in water (e.g., toluene), with low water activity (a w ). In this review, we use the definition whereby lipases hydrolyze triacylglycerols or acyl esters with acyl chains of 10 carbons or more.…”
Section: Lipases: General Features and Classical Strategy Of Immobilizationmentioning
confidence: 99%
“…Esterase break ester bonds of shorter chain fatty acids, while lipase display a much broader substrate range, including long‐chain fatty acids (Delgado‐García et al., 2018). Lipases are capable of hydrolyzing insoluble or aggregated substrates, while esterases are highly effective toward soluble substrates (Bracco et al., 2020; Reyes‐Duarte, Coscolín, Martínez‐Martínez, Ferrer, & García‐Arellano, 2018). Because both enzymes have similar substrate specificity, they can be expressed from the same microorganism.…”
Section: Categories and Applications Of Food Enzymes From Extremophilesmentioning
confidence: 99%
“…Because both enzymes have similar substrate specificity, they can be expressed from the same microorganism. Majority of lipases and esterases share the same α/β hydrolase fold and are sometimes difficult to differentiate by primary sequence comparisons, structural features, and kinetic parameters (Bracco et al., 2020; Vaquero, de Eugenio, Martínez, & Barriuso, 2015). For instance, Candida antarctica lipase B (Cal B) acts as a lipase when adsorbed to an acylglyceride interface and as an esterase when exposed to an aqueous environment (Benson & Pleiss, 2017).…”
Section: Categories and Applications Of Food Enzymes From Extremophilesmentioning
confidence: 99%
“…However, biphasic systems that contain large amounts of water allow adequate hydration of the biocatalyst. Recently, Bracco et al have shown that a w is a suitable parameter to distinguish between lipases and esterases [ 58 ]. Although some lipases (such as those derived from CALB and R. arrhizus ) maintain good activity at low water content, other lipases require higher water activity levels to show good catalytic activity—e.g., lipase from P. cepacian [ 59 ].…”
Section: Introductionmentioning
confidence: 99%